Current Trends in Development of Liposomes for Targeting Bacterial Biofilms - Zora Rukavina; Željka Vanić (MDPI AG, 2016)
Biofilm targeting represents a great challenge for effective antimicrobial therapy. Increased biofilm resistance, even with the elevated concentrations of very potent antimicrobial agents, often leads to failed therapeutic outcome. Application of biocompatible nanomicrobials, particularly liposomally-associated nanomicrobials, presents a promising approach for improved drug delivery to bacterial cells and biofilms. Versatile manipulations of liposomal physicochemical properties, such as the bilayer composition, membrane fluidity, size, surface charge and coating, enable development of liposomes with desired pharmacokinetic and pharmacodynamic profiles. This review attempts to provide an unbiased overview of investigations of liposomes destined to treat bacterial biofilms. Different strategies including the recent advancements in liposomal design aiming at eradication of existing biofilms and prevention of biofilm formation, as well as respective limitations, are discussed in more details.